A Comprehensive and Additive System for Child-Focused Assessment and Evaluation in EI/ECSE - Bricker, Diane; Squires, Jane; Xie, Huichao (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
One of the more serious problems facing the field of early intervention/early childhood special education is the disconnect between the community programs that offer screening, eligibility determination, curricular assessment (i.e., programmatic assessment), and progress monitoring services. First, we provide definitions of these service components to ensure clarity. Second, the substantial disconnect found between the screening, eligibility determination, curricular assessment, and progress monitoring components in most communities is discussed. Third, an alternative conceptual framework and its rationale are offered. This framework is designed to ensure that information collected is comprehensive, and that information/data gathered during each component serves as the platform for the next component. An example clarifies the application of the framework.